Corporate Social Responsibility and Financial Performance: The Moderating Role of Firm Size - Fiana, Fiana; Endri, Endri (International Journal of Economics and Financial Issues, 2025)
The study aims to investigate the impact of Corporate Social Responsibility (CSR) and other bank-specific factors, namely Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Loan Deposit Ratio (LDR) on financial performance moderated by company size. Financial performance is proxied by Return on Asset (ROA). The research sample consisted of 13 conventional banks listed on the Indonesia Stock Exchange from 2019 to 2023. The study’s results found that CAR negatively impacted ROA, but if interacted with company size, the relationship became positive. NPL had a negative effect on ROA in a model without a moderator role, and vice versa; it had a positive impact. The interaction of NPL and company size had a negative effect on ROA. LDR had a negative relationship with ROA, but if it interacted with company size, it had a positive impact. CSR positively impacted ROA in a model without moderation, but vice versa had a significant relationship. The interaction of CSR with company size also had no impact on ROA. Company size directly affected ROA. The implications of the empirical findings provide recommendations for policymakers, corporate management, academics, and investors to pay attention to the importance of CSR practices and specific factors to improve bank financial performance.